(untitled) (Kronika Bydgoska, 2010)
The Polish literaturę published so far about the liberation of Bydgoszcz from the German occupation disregarded this problem, writing about a relatively quick and smooth seizure of the city by the Red Army and the Polish Army. The reviewed work based on numerous sources shows a different picture of the events. On January 24-27, 1945, fierce fights waged in the streets of the city took heavy casualties.